Space, Patronage, and Ritual Art: Steles in the Guyang Cave (Late 5th–Early 6th Century) - Dongshan Zhang (Religions)
The Guyang Cave contains an extensive collection of late Northern Wei (late fifth to early sixth century) statue and stele combinations. While existing scholarship has recognized the exceptional nature of these statue–stele pairings, their systematic stylistic classification and contextual interpretation have yet to receive sustained scholarly attention. This investigation analyzes ten paradigmatic cases, organized into three distinct stylistic groups. The discussion subsequently focuses on four particularly representative examples that epitomize divergent approaches to stele implementation. These stylistic differentiations emerge as direct responses to specific spatial contingencies within the cave’s architecture. Instead of being merely decorative, these innovative configurations served as ritual instruments, amplifying patrons’ devotional objectives within the cave’s competitive environment. Ultimately, this study contributes to the theoretical discourse on “ritual art” by revealing how spatial negotiations between patrons manifested as a dynamic ritual process—one that both informed and was sustained by artistic creation in the Guyang Cave. More broadly, in the late Northern Wei period, artistic expression and ritual practice emerged as mutually constitutive elements in the dynamic formation of religious and cultural traditions.